Flexible antibacterial Zr-Cu-N thin films resistant to cracking; Journal of Vacuum Science and Technology A; Vol. 34, iss. 2 - Musil Y. Yindrikh; Zitek M. Michal; Fajfrlik K. Karel; Cerstvy R. Radomir (2015, 2015)
Title screen